Comparing laser speckle contrast imaging and indocyanine green angiography for assessment of parathyroid perfusion - Emmanuel A. Mannoh; Naira Baregamian; Giju Thomas; Carmen C. Solόrzano; Anita Mahadevan-Jansen (Scientific Reports, 2023)
Abstract Accurate intraoperative assessment of parathyroid blood flow is crucial to preserve function postoperatively. Indocyanine green (ICG) angiography has been successfully employed, however its conventional application has limitations. A label-free method overcomes these limitations, and laser speckle contrast imaging (LSCI) is one such method that can accurately detect and quantify differences in parathyroid perfusion. In this study, twenty-one patients undergoing thyroidectomy or parathyroidectomy were recruited to compare LSCI and ICG fluorescence intraoperatively. An experimental imaging device was used to image a total of 37 parathyroid glands. Scores of 0, 1 or 2 were assigned for ICG fluorescence by three observers based on perceived intensity: 0 for little to no fluorescence, 1 for moderate or patchy fluorescence, and 2 for strong fluorescence. Speckle contrast values were grouped according to these scores. Analyses of variance were performed to detect significant differences between groups. Lastly, ICG fluorescence intensity was calculated for each parathyroid gland and compared with speckle contrast in a linear regression. Results showed significant differences in speckle contrast between groups such that parathyroids with ICG score 0 had higher speckle contrast than those assigned ICG score 1, which in turn had higher speckle contrast than those assigned ICG score 2. This was further supported by a correlation coefficient of -0.81 between mean-normalized ICG fluorescence intensity and speckle contrast. This suggests that ICG angiography and LSCI detect similar differences in blood flow to parathyroid glands. Laser speckle contrast imaging shows promise as a label-free alternative that overcomes current limitations of ICG angiography for parathyroid assessment.